Inhibitory Effect of Cudratrixanthone U on RANKL-Induced Osteoclast Differentiation and Function in Macrophages and BMM Cells - Kim, Eun-Nam; Kwon, Jaeyoung; Lee, Hyun-Su; Lee, Sooyeun; Lee, Dongho; Jeong, Gil-Saeng (Frontiers in Pharmacology, 2020)
Cudratrixanthone U (CTU) is a prenylated xanthone compound isolated from Maclura tricuspidata Bureau (Moraceae). Prenylated xanthones have been reported to exhibit a variety of biological activities. However, the effects of prenylated xanthone on osteoclast differentiation and function are still unclear. Excessive bone resorption by osteoclasts is considered a major cause of diseases such as osteoporosis. Accordingly, suppression of excessive osteoclast formation and function is one of strategies for treating osteoclast related bone diseases. In this study, CTU inhibited osteoclast differentiation and function in RAW264.7 macrophages and BMM cells induced by receptor activator of nuclear factor-κB ligand (RANKL). CTU regulated the formation of TRAF6-TAK1 complex in RANKLinduced RAW264.7 macrophages and BMM cells. Osteoclast-specific genes including those encoding matrix metallopeptidase 9 (MMP-9), dendritic cell-specific transmembrane proteins (DC-STAMP), cathepsin K (CTSK) and chemokine CC motif ligand 4 (CCL4) play an important role in bone resorption and migration, and were effectively regulated by CTU.These results suggest that CTU is a potential therapeutic agent in osteoporosis.